Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I have been looking at the following:

P entails Q implies P

And developed the proof as follows:

1. P
2. Q (Start of new subproof)
2.1 P (By 1)
3 Q implies P by INTRODUCTION OF IMPLICATION 2, 2.1

However, while it makes sense in terms of logic, I can't get it's general meaning.

To me, this is like saying: "I have P. Assuming I have Q, I still have P. So Q must imply P."

Or: "It's raining. Assuming I don't have an umbrella, it's still raining. So the fact I don't have an umbrella implies it's raining."

Is this proof simply stating that whatever assumption, the base assumptions will still hold, so it's trivially true, or...?

share|improve this question

3 Answers 3

up vote 7 down vote accepted

One nice way to make sense of what is happening: We have that $P$.

Assume we have $Q$, and reassert what we know we have: $P$.

Then we conclude that "If we have $Q$, then we have $P$, which we symbolize by $\;Q\rightarrow P$.

It so happens that in this case, we have $P$ even when we don't have $Q$, but that doesn't matter, since any implication with a true consequent (in this case $P$) holds.


Note also that from the premise $P$, we can derive $\lnot Q \lor P$ by $\lor$ introduction. And $\lnot Q\lor P \equiv Q\rightarrow P$, and indeed that equivalence can be derived if needed.

share|improve this answer
    
Interestingly enough in 3-valued logic, CpCqp is a tautology even though EANpqCpq is not a tautology. –  Doug Spoonwood Jun 8 at 22:42

No, it's just that it's only valid to say that "$Q \Rightarrow P$" is false if $Q$ is true and $P$ is false. Suppose your friend calls you up and tells you "If I manage to find a cab, I'll be there in five minutes". And he does show up in five minutes, but not in a cab. He hitched a ride. Would you say your friend lied? No, he just said that if he gets a cab, he'd reach in five minutes. He didn't say "otherwise I won't".

share|improve this answer

Use: $Q\implies P$ is equivalent to $\neg(Q \land \neg P)$

  1. Assume $P$

  2. Assume $Q\land \neg P$

  3. $\neg P$ (Elim $\land$, from 2)

  4. $P \land \neg P$ (Intro $\land$, 1, 3)

  5. $\neg (Q \land \neg P)$ (Conclusion, from 2, 4)

  6. $Q\implies P$ (Equivalence, from 5)

  7. $P\implies (Q\implies P)$ (Conclusion, from 1, 6)

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.